2017
DOI: 10.1177/0748233717733598
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and di(2-ethylhexyl) phthalate exert divergent effects on apoptosis and the Wnt/β-catenin pathway in zebrafish embryos: A possible mechanism of endocrine disrupting chemical action

Abstract: Polyethylene terephthalate (PET) and polycarbonate (PC) are the most commonly used plastics in water bottles. Di(2-ethylhexyl) phthalate (DEHP) is used as a plasticizer in PET plastics, and bisphenol A (BPA) is used to produce PC. Both DEHP and BPA are known for their potential endocrine disrupting effects. The Wnt/β-catenin signaling pathway has important roles in cell proliferation, cell specification and cell fate determination during embryonic development. Recent reports suggest a link between the Wnt/β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…PCRs were performed using the DNA Master SYBR Green kit (Qiagen). PCRs were performed using the DNA Master SYBR Green kit (Qiagen) 51 . The expression of aanat2 (forward primer 5′-3′: AGGACGCCATCAGTGTGTTT; reverse primer 5′-3′: CTGGCCCAGGAAAACAAGTA), mtnr1ba (forward primer 5′-3′ CATTGGTCCCTGATTGGCTG; reverse primer 5′-3′ GTCCCGCCTTTTGATGTCTC) and pax7b (forward primer 5′-3′: GGAACAGTACCGCGAATGAT; reverse primer 5′-3′: GAATACACCGCCAAGCTGAT) were evaluated by quantitative RT-PCR using the Qiagen Rotor Gene-Q Light Cycler instrument.…”
Section: Methodsmentioning
confidence: 99%
“…PCRs were performed using the DNA Master SYBR Green kit (Qiagen). PCRs were performed using the DNA Master SYBR Green kit (Qiagen) 51 . The expression of aanat2 (forward primer 5′-3′: AGGACGCCATCAGTGTGTTT; reverse primer 5′-3′: CTGGCCCAGGAAAACAAGTA), mtnr1ba (forward primer 5′-3′ CATTGGTCCCTGATTGGCTG; reverse primer 5′-3′ GTCCCGCCTTTTGATGTCTC) and pax7b (forward primer 5′-3′: GGAACAGTACCGCGAATGAT; reverse primer 5′-3′: GAATACACCGCCAAGCTGAT) were evaluated by quantitative RT-PCR using the Qiagen Rotor Gene-Q Light Cycler instrument.…”
Section: Methodsmentioning
confidence: 99%
“…We have also investigated the relation between Wnt signaling, apoptosis, and proliferation in BPA exposed zebrafish embryos. We reported that BPA exposure led to increased vitellogenin levels, apoptosis, and gsk3β expressions in zebrafish embryos (Üstündağ et al, 2017b). Similar to the results of our study, WNT3a has been reported to induce pro-apoptotic changes in the intrinsic apoptotic pathway, including BCL2L11, BBC3, and MCL1 (Zimmerman et al, 2013).…”
Section: Effects Of Edcs On Wnt Pathwaymentioning
confidence: 98%
“…Our group has shown that DEHP exposure led to increased mRNA levels of gsk3β in zebrafish embryos (Üstündağ et al, 2017b). We have also investigated the relationship between oxidant-antioxidant status and the Wnt/β-catenin target proto-oncogene c-myc expression in DEHP (2.5 μg/L) exposed zebrafish embryos.…”
Section: Effects Of Edcs On Wnt Pathwaymentioning
confidence: 99%
“…Reverse osmosis water was used for the experiments and the water was supplemented with 0.018 mg L −1 Instant Ocean™ salt. After their natural spawnings the fertilized embryos were gathered then they were cultured, and they were staged according their developmental time and morphological criteria based on the methods that were described previously (4,6). Since embryos used in this study were younger than 5 days old, no licence is needed by Council of Europe (1986), Directive 86/609/EEC or Marmara University ethics committee.…”
Section: Maintenance Of Zebrafishmentioning
confidence: 99%